2019
DOI: 10.3389/fmed.2019.00175
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Older People: Concepts and Controversies

Abstract: Atrial fibrillation (AF) is the commonest cardiac rhythm abnormality and has a significant disease burden. Amongst its devastating complications is stroke, the risk of which increases with age. The stroke risk in an older person with AF is therefore tremendous, and oral-anticoagulation (OAC) therapy is central to minimizing this risk. The presence of age-associated factors such as frailty and multi-morbidities add complexity to OAC prescription decisions in older patients and often, OAC is needlessly withheld … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 155 publications
(162 reference statements)
0
61
1
6
Order By: Relevance
“…in case of paroxysmal atrial fibrillation). However, such initially cryptogenic stroke patients are younger and have less comorbidities compared to the standard cardioembolic stroke patients [ 18 ]. The exclusion of such patients as it was done by the MR-CLEAN investigators might therefore explain the reported baseline imbalances in their subgroup analysis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…in case of paroxysmal atrial fibrillation). However, such initially cryptogenic stroke patients are younger and have less comorbidities compared to the standard cardioembolic stroke patients [ 18 ]. The exclusion of such patients as it was done by the MR-CLEAN investigators might therefore explain the reported baseline imbalances in their subgroup analysis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The prevalence of FS increases with age and may significantly affect both treatment success and the ultimate outcomes of AF. 11 It is estimated at 7-12% of the elderly population. Between the ages of 56 and 74, FS is diagnosed in 3.9% of patients, but in patients aged over 85, this proportion increases to 25%.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we identified frailty syndrome in 34.2% of patients, and more often among the women. 17,18 Many authors have undertaken research whose aim was to assess the factors that affect the effectiveness of electrical cardioversion. Among the factors that influence the effectiveness of cardioversion are the elimination of the cause of arrhythmias, the duration of arrhythmia, age, obesity, mitral valve defects, left atrial enlargement, number of previous relapses, atrial conduction disturbances and a higher heart rate.…”
Section: Discussionmentioning
confidence: 99%